2010
DOI: 10.1002/jmri.22174
|View full text |Cite
|
Sign up to set email alerts
|

Pulse sequence and timing of contrast‐enhanced MRI for assessing blood–brain barrier disruption after transcranial focused ultrasound in the presence of hemorrhage

Abstract: Purpose: To optimize the timing of contrast-enhanced magnetic resonance imaging (MRI) that best indicates blood-brain barrier (BBB) disruption induced by focused ultrasound (FUS) along with an ultrasound contrast agent (UCA) and to verify that the contrast-enhanced spin-echo MRI sequence can indicate the degree and location of BBB disruption in the presence of hemorrhage better than a gradient-echo sequence. Materials and Methods:Sonication was applied to 12 rat brains with four different doses of UCA to cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The magnitude has been found to increase with the burst length up to a duration of approximately 10 ms, with further increases in burst length having little or no effect [77,81,86,90,9092]. Several groups have shown that the disruption magnitude may be increased by using a larger dose of ultrasound contrast agent [83,9395] (although other works have shown little or no effect [86,90]) or by using larger microbubbles [8789]. Pulse repetition frequency can also influence the magnitude of disruption up to a point [90,91], but other studies have seen no dependence [86].…”
Section: Ultrasound-induced Bbb Disruptionmentioning
confidence: 99%
“…The magnitude has been found to increase with the burst length up to a duration of approximately 10 ms, with further increases in burst length having little or no effect [77,81,86,90,9092]. Several groups have shown that the disruption magnitude may be increased by using a larger dose of ultrasound contrast agent [83,9395] (although other works have shown little or no effect [86,90]) or by using larger microbubbles [8789]. Pulse repetition frequency can also influence the magnitude of disruption up to a point [90,91], but other studies have seen no dependence [86].…”
Section: Ultrasound-induced Bbb Disruptionmentioning
confidence: 99%
“…Neuronal nuclei were counted in a microscope field from the center of the sonication and from a field adjacent to the disrupted region (nonsonicated with a 7.0-T small-bore MR imaging unit (BioSpec 70/30 USR; Bruker, Billerica, Mass). T2-weighted and T2*-weighted images were obtained by using the parameters outlined in the Table. High signal intensity on T2-weighted images was considered to be a sign of residual edema and possible lesion formation, while T2*-weighted images were used to determine if bleeding or large extravasations of red blood cells had occurred (22,23).…”
Section: Control Algorithm Performancementioning
confidence: 99%
“…Using a different set of FUS parameters with higher UCA dosage, however, we demonstrated that the contrast enhancement in the spin echo T 1 W sequence was correlated with both the UCA dosage and the degree of BBB disruption quantified by EB extravasation (28). In this study, we further demonstrated that the correlations between MR and UCA dosage as well as the correlations between MR and EB The sonication was applied to the right hemisphere, the left hemisphere was left intact.…”
Section: Correlation Between Mr and Uca Dosagementioning
confidence: 54%
“…It is known that ultrasound pressure, burst length, and FUS duration can influence the degree of BBB disruption. Our previous study showed that using 1.2 MPa (peak negative pressure), a burst length of 50 msec and sonication duration of 60 sec could cause severe hemorrhage (28). To avoid severe hemorrhage and tissue damage, we reduced ultrasound pressure to 0.56 MPa, burst length to 10 msec, and sonication duration to 20 sec in this study.…”
Section: Nonhemorrhagic Vs Biosafety Conditionsmentioning
confidence: 97%